2021
DOI: 10.1021/acsnano.0c09553
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Accumulating Nanoparticles for Assisting Astrocytes to Reduce Human Immunodeficiency Virus and Drug Abuse-Induced Neuroinflammation and Oxidative Stress

Abstract: Human neurotropic immunodeficiency virus (HIV) ingress into the brain and its subsequent replication after infection results in viral reservoirs in the brain. The infected cells include microglia, perivascular macrophages, and astrocytes. HIV-associated neurocognitive disorders (HAND) affect glial cells by activating microglia and macrophages through neuroinflammation, as well as astrocytes through mitochondrial dysfunctions and the onset of oxidative stress, impairing the ability of these cells to engage in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Internalization of NPs by astrocytes is relevant in the context of the main role played by these cells in protective and deleterious pathophysiological mechanisms, such as during secondary lesion development in TBI or neurodegenerative disorders ( 99 103 ). Consistent with our findings, some polymeric NPs have been proven to be useful as carriers for antiretroviral therapy in combination with antioxidant and anti-inflammatory neuroprotectants into astrocytes, reducing the oxidative stress and neuroinflammation caused by human neurotropic immunodeficiency virus ( 104 ). Also, biodegradable PLGA NPs have even been used for gene delivery into astrocytes aiming to compensate for astrocytic dysfunction linked to neurodegeneration ( 103 ).…”
Section: Discussionsupporting
confidence: 87%
“…Internalization of NPs by astrocytes is relevant in the context of the main role played by these cells in protective and deleterious pathophysiological mechanisms, such as during secondary lesion development in TBI or neurodegenerative disorders ( 99 103 ). Consistent with our findings, some polymeric NPs have been proven to be useful as carriers for antiretroviral therapy in combination with antioxidant and anti-inflammatory neuroprotectants into astrocytes, reducing the oxidative stress and neuroinflammation caused by human neurotropic immunodeficiency virus ( 104 ). Also, biodegradable PLGA NPs have even been used for gene delivery into astrocytes aiming to compensate for astrocytic dysfunction linked to neurodegeneration ( 103 ).…”
Section: Discussionsupporting
confidence: 87%
“…BBB-penetrating polymeric nanoparticles containing ARVs, antioxidant CoQ10 and a pro-drug of aspirin. Reproduced with permission from reference . Copyright 2021 American Chemical Society.…”
Section: Specific Diseasesmentioning
confidence: 99%
“…The in vitro coculture (human astrocytes and microglia cells) and in vivo EcoHIVinfected methamphetamine-exposed animal model show improved protection of microglia, neurons and astrocytes (Figure 8). 93 In 2021 a solid dispersed material was developed with dispersed DTG and poloxamer 407 and was checked in vitro and in vivo; it showed an increased rate of dissolution with enhanced bioavailability. 94 The polymeric material Eudragit-100 was used as a taste masking agent for the orally disintegrating tablet cotrimoxazole (CTX).…”
Section: Aids (Hiv)mentioning
confidence: 99%
“…Endogenous antioxidants such as coenzyme Q10, glutathione and melatonin are, therefore, potential and promising targets for anti-aging therapy and could prevent brain inflammaging effects [ 181 ]. In that direction, we have shown that a targeted delivery of COQ 10 prevented cellular senescence and oxidative stress in neural progenitor cells and astrocytes treated with antiretroviral drugs, exposed to drugs of abuse or infected with HIV-1 [ 182 , 183 ]. Moreover, exogenous melatonin treatment prevented neuroinvasion and cerebrovascular abnormalities in K18-hACE2 mice [ 184 ], thus corroborating a protective role of antioxidant therapy in Neuro-COVID-19.…”
Section: Aging and Mitochondrial Dysfunction In Bbb Neuroinflammationmentioning
confidence: 99%